Pengaruh Keberadaan Mangrove Terhadap Tanggul Pantai (Studi Kasus Tanggul Pantai NCICD di Jakarta) - Huda Bachtiar; Muhammad Fahrul Saifullah; Semeidi Husrin; Leo Sembiring; I Putu Samskerta; Ketut Darma (JURNAL TEKNIK HIDRAULIK, 2017)
North Jakarta sinks over time and it needs immediate solution to countermeasure flooding from the sea side. One of National Capital Integrated Coastal Development Program (NCICD)is Phase A. The Phase-A program is the construction of coastal dike,, river dike, and also polder system for the short term period. The coastal diike and river dike lengths are 120 km. One of the typical dike of the Phase A is green dike. This is the combination of dike and mangrove forest in front of it. This paper discusses the impact of exixtence mangrove infront the dike from the hydraulic analyses point of view. The physical model test was carried out in the Experimental Station for Coastal under Research Center for Water Resources Laboratory, Buleleng-Bali. 204 scenarios were tested for the experiments with considering mangrove densit, wave height, wave period, and variation of the water depth; condition without exixtence of dike and mangrove (TTTM), with dike and without mangrove (DTTM), and with dike and with mangrove (DTDM). DTDM scenarios are also divided into width of the forest and the mangrove density. The simulation results yield that the exixtence of mangrove provide significant impact on wave transmision and wave dissipation. The exixstence of wangrove forests can reduce the wave dissipation energy into 60-90%.